Analysis of overhead ground wire sizes in distribution systems - T. Thanasaksiri (2018)
This paper presents an approach to analyze the overhead ground wire (OHGW) sizes in distribution system focus on the i2t of line to ground fault current. For line to ground fault, the fault current and duration time when fault take place as well as the relay operting time have been concerned. The Line Type I, OHGW not connected to the neutral of substation power transformer, give the short circuit current magnitude which is less than the current from Line Type II, OHGW connected to the neutral of substation power transformer. So the Line Type I gives the smaller OHGW sizes than Line Type II. For the short circuit current not greater than 3 kA, the 25 mm2 can be used for the distance of 3 km from substation and 35 mm2 from that location should be used. For the short circuit current not greater than 7 kA, the 35 mm2 should be used for distance of 500 m from the substation, 70 mm2 between 500 m-3 km and the 35 mm2 beyond that location should be used. For the short circuit current not greater than 12 kA, the 50 mm2 should be used for 500 m from substation, 70 mm2 should be used between 500 m-3 km and 35 mm2 for line beyond that location should be used. ©2009 IEEE.